Technical writing - Sebastian, Evelyn L.; Asuncion, Risa P. (Quezon City, Philippines : Maxcor Publishing House Inc., 2014)
This book is further designed to show the different models that can help students write concise and organized document meant for specific readers.
Chapter I What is technical writing -- Chapter II Characteristics of technical writing -- Chapter III Technical writing style -- Chapter IV Description of mechanism -- Chapter V Description of a process -- Chapter VI Classification -- Chapter VII Outline and abstracts -- Chapter VIII Report writing -- Chapter IX Graphics -- Chapter X Business letters and memos -- Chapter XI Technical presentation.
Includes bibliographical references.
Keywords: TECHNICAL WRITING